Types of Force and Their Utilization: Guided Inquiry-Based Interactive E-LKPD for Fourth Grade Elementary School Students - Indrawan, I Ketut Ogik; Yudiana, Kadek (MIMBAR PGSD Undiksha, 2022)
There are still many science learning activities that are less fun. Learning activities are still teacher center. It causes students to lack focus. It has an impact on science learning outcomes. This research aims to create an interactive E-LKPD based on guided inquiry on the science content of various styles of material and their use for fourth-grade elementary school students. This type of research is development research with the ADDIE model. The research subjects were six people consisting of two material experts, two media experts, and two practitioner experts. The subject of the product trial was fourth-grade elementary school students, totaling ten students. The method of collecting data is a questionnaire. The instrument used is a questionnaire. The data analysis techniques are descriptive, qualitative, and quantitative. The study results are that the average assessment given by learning media experts is 47, so they get very good qualifications. The average assessment given by learning material experts is 46.5, so they get very good qualifications. The average assessment given by the teacher is 62.5, and the student response is 47.8, so the qualifications are very good. So, the Guided Inquiry-Based Interactive E-LKPD on Science Content is valid and feasible to use in the learning process. This research implies that teachers can use guided inquiry-based interactive E-LKPD in the learning process.